Bilateral lung transplantation in a 9‐year‐old girl with bronchopulmonary dysplasia with pulmonary hypertension. Issue 10 (5th August 2021) - Ota, Chiharu; Saito, Ryoko; Tominaga, Junya; Iwasawa, Shinya; Hirama, Takashi; Matsuda, Yasushi; Ono, Katsunori; Onoki, Takehiko; Kimura, Masato; Kawabata, Yoshinori; Okada, Yoshinori
Abstract: Background: Bronchopulmonary dysplasia (BPD) is a chronic respiratory disease that occurs in premature infants and the prognosis is variable depending on the comorbidities including fibrosis, emphysema, or pulmonary hypertension (PH). We present a case of a 9‐year‐old girl who developed PH associated with severe BPD (BPD‐PH) and underwent bilateral lung transplantation (BLTx). Case description A 9‐year‐old girl was admitted to our department to undergo BLTx. She was born at 23 weeks and 4 days gestation with a weight of 507 g. She received ventilation for the first 2 months and required further respiratory care due to repetitive, severe respiratory infections. She was diagnosed with BPD‐PH at 6 months of age and oral administration of pulmonary vasodilators were initiated. She was registered as a lung transplant candidate at 4 years of age after the life‐threatening exacerbation. Chest computed tomography (CT) revealed severe lung conditions with ground‐glass opacities and emphysematous low‐density areas in the upper and lower lobes. BLTx from a brain‐dead male donor was performed. The pathological findings of her resected lung revealed saccular, hypoplastic lung with alveolar repair/regeneration, and medial hypertrophy and muscularization of peripheral arteries. The postoperative course was mostly uneventful. She was free from oxygen administration and showed no signs of PH after 6 months of the surgery. Conclusion: This is the first case report of BLTx in a pediatric, irreversible BPD‐PH patient with detailed pathohistological findings and clinical examination. Lung transplantation is one of the treatment options for severe BPD‐PH.